Mutant p53 Gain-of-Function in Cancer - Oren, Moshe (Cold Spring Harbor Laboratory Press, 2010)
In its wild-type form, p53 is a major tumor suppressor whose function is critical for protection against cancer. Many human tumors carry missense mutations in the TP53 gene, encoding p53. Typically, the affected tumor cells accumulate excessive amounts of the mutant p53 protein. Various lines of evidence indicate that, in addition to abrogating the tumor suppressor functions of wild-type p53, the common types of cancer-associated p53 mutations also endow the mutant protein with new activities that can contribute actively to various stages of tumor progression and to increased resistance to anticancer treatments. Collectively, these activities are referred to as mutant p53 gain-of-function. This article addresses the biological manifestations of mutant p53 gain-of-function, the underlying molecular mechanisms, and their possible clinical implications.